Transparansi Pengelolaan Anggaran Di Kelurahan Winangun Satu Kecamatan Malalayang Kota Manado - Stevani Ribka Eunike Sondakh; Arie Junus Rorong; Joorie Ruru (JURNAL ADMINISTRASI PUBLIK, 2023)
​The purpose of this research is to find out/explain the implementation of transparency management in Winangun sub-district, one Malalayang sub-district, Manado city. This research uses a descriptive research method with a qualitative approach. The informants used in this study were the head of the Winangun 1 sub-district, and staff in the Winangun 1 sub-district, the Malalayang sub-district head, the Malalayang sub-district budget management department, and the Winangun 1 sub-district community. The importance of focusing on this research so as not to run away from the context of the discussion that will be studied, the researcher uses the theory of Informative transparency, Disclosure, Disclosure. Data collection techniques used are observation, interviews, and document studies. From the results of the research, budget management is not yet transparent because it is managed by the sub-district government, which should be known to the public, either in the form of billboards or facilities that can be used to minimize the lack of transparency in the kelurahan. Keywords: Transparency, Budget Management, Kelurahan